2015
DOI: 10.1186/s13059-015-0589-1
|View full text |Cite
|
Sign up to set email alerts
|

High-depth sequencing of over 750 genes supports linear progression of primary tumors and metastases in most patients with liver-limited metastatic colorectal cancer

Abstract: BackgroundColorectal cancer with metastases limited to the liver (liver-limited mCRC) is a distinct clinical subset characterized by possible cure with surgery. We performed high-depth sequencing of over 750 cancer-associated genes and copy number profiling in matched primary, metastasis and normal tissues to characterize genomic progression in 18 patients with liver-limited mCRC.ResultsHigh depth Illumina sequencing and use of three different variant callers enable comprehensive and accurate identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 37 publications
6
45
0
Order By: Relevance
“…Indeed, this was the case in both CRC patients in which the driver mutations (APC, KRAS, TP53, NRAS, CDK4) were found in both the primary and metastatic organ sites. These data are also consistent with previous NGS data that have reported a high concordance of primary and metastatic tumor mutations (Brannon et al 2014;Tan et al 2015).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, this was the case in both CRC patients in which the driver mutations (APC, KRAS, TP53, NRAS, CDK4) were found in both the primary and metastatic organ sites. These data are also consistent with previous NGS data that have reported a high concordance of primary and metastatic tumor mutations (Brannon et al 2014;Tan et al 2015).…”
Section: Discussionsupporting
confidence: 82%
“…Further work has begun to investigate the mutational concordance of matched primary and metastatic tumors in CRC patients by next-generation sequencing. In a study that profiled microsatellite-stable (MSS) CRC patients, a large number of mutations were reported as being concordant between the primary and metastatic tumors, in addition to a small number of metastasis-specific mutations (Brannon et al 2014;Tan et al 2015).…”
mentioning
confidence: 99%
“…In particular, we wanted to be able to simultaneously assay for the presence of multiple somatic mutations identified from the CRC primary tumour in patient plasma and determine the correlation with clinical events. In CRC, because of the high degree of genomic similarity of the primary and metastases1011, the resected surgical specimen provides an available mutational profile to monitor and or provide diagnostic support for the recurrence of the same cancer. Similar studies have recently shown that ctDNA can be detected in CRC patients post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that used tumour tissue to determine mutations to monitor in ctDNA used tissue fairly contemporary to the plasma assayed. However, we and others showed that there is a large degree of genomic concordance amongst somatic mutations (about 80%) in each patient’s primary tumour and corresponding metastatic lesion1011. This suggested that we could indeed use somatic mutations identified from a patient’s surgical primary CRC specimen to provide an individualised “nucleic acid thumbprint” for detection in plasma at metastasis, specific not only to the patient, but also to the particular cancer.…”
mentioning
confidence: 87%
“…Two of the four mutations (p.D351H and p.R361H) are well-known pathological mutations, and the other two missense mutations (p.G352E and p.A532D) are relatively infrequent mutations. The presence of p.G352E was reported in colorectal cancer (32), squamous cell lung cancer (33) and pancreatic cancer in the COSMIC (v74) database (34); p.A532D was identified in colorectal and pancreatic cancer in the COSMIC (v74) database (35). These two mutations were identified as pathological mutations following in silico analysis, including SIFT, PolyPhen and PANTHER.…”
Section: Resultsmentioning
confidence: 99%